Ketidakpastian Model SWAT di Daerah Aliran Sungai Berlahan Sawah Irigasi - Hanhan Ahmad Sofiyuddin; Tasuku Kato; Ryota Tsuchiya (Balai Teknik Irigasi, 2016)
Soil and Water Assessment Tool (SWAT) is a very promising model in an agricultural watershed. However, the modeling approach could include uncertainties in its model structures especially if it is applied in watershed consisting irrigated paddy fields. This is due to SWAT was initially developed to model dry land agricultural area so that there were some different assumptions or model structures compared to common understanding in paddy field. However, the significance of model structure uncertainty to overall model performance is not yet clearly be understood. This study is aimed to analyze the performance, applicability, and uncertainties of SWAT (original/modified) to model watershed containing irrigated paddy field. The analysis was conducted through model structure evaluation and uncertainty analysis using the Sequential Uncertainty Fittin (SUFI-2) method by considering several SWAT model configurations, i.e. original and modified version. As the result, SWAT model structure cannot adequately represent the surface storage, seepage, and irrigation process in paddy field. Through calibration, these inadequate representation could be improved to have a better overall model performance indexes. However, significant difference in performance could be observed through uncertainty analysis. Modified SWAT model have better reliability i.e. narrower uncertainty band especially during low flow period. These results also imply that surface storage, seepage, and irrigation are some of the most important processes for hydrological simulation in irrigated paddy field watershed.